Paradoks Kota Santri: Kajian Sosiologis Pengelolaan Sampah Di Kecamatan Soppeng Riaja Kabupaten Barru - Darwis, Ihsan; Nasruddin, Nasruddin; Rahmaniah, Nurul (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study examines the paradox in Soppeng Riaja District, Barru Regency, which is known as a “santri city” but faces serious problems in waste management. Religious identities that emphasize cleanliness are not fully reflected in people's social behavior. This research aims to explore the social dynamics behind these problems and examine the role of educational institutions, society, and the government in formulating relevant solutions. With a sociological approach, the analysis is focused on how social constructions of cleanliness are formed, as well as the extent to which religious norms and government policies affect the collective behavior of society. The results of the study show that the main obstacles in waste management in Soppeng Riaja include low collective awareness, limited infrastructure, and weak coordination between parties. This research is expected to contribute to the development of policies based on socio-religious values to increase environmental awareness, as well as enrich the sociological study of social identity and environmental sustainability in religious societies.